Virtual care: a 'Zoombie' apocalypse?. (17th September 2020) - Shachak, Aviv; Alkureishi, Maria Alcocer
Abstract: In the wake of COVID-19, clinicians took to telehealth to continue providing services to their patients, mostly via telephone or videoconferencing technology. Telehealth has many promised and proven benefits including convenience to the patient, potentially less distraction from the electronic health record (EHR), saves in travel time and expenses, and lowering patients' wait time in the clinic. However, there could be some unintended negative consequences including increased clinician burnout due to screen fatigue, potential loss of information due to the limitations of the medium, difficulty discussing sensitive issues and impacts on patient-clinician relationship, empathy, and compassion. In this perspective, we discuss some of the positives and potential negatives of telehealth and highlight some considerations that could guide the choice of media. We submit that for telehealth to become a sustainable solution that is widely applied, it is important to take these issues into consideration in both research and implementation of telehealth solutions.